Implementasi Metode Al-Miftah Untuk Meningkatkan Kemampuan Santri Dalam Membaca Kitab Kuning - Imam Fathoni, Ahmad; Syamsul A’dlom (PAI RAFAH, 2024)
This study examines the implementation of the Al-Miftah method to improve the ability of students to read the yellow book at the Raudlatul Ulum 1 Islamic Boarding School, Ganjaran Village, Gondanglegi District, Malang Regency. This research uses qualitative research methods by collecting data in the form of words and descriptions. Data were obtained through interviews, field notes, photos, videos, personal documents, and other documents. The main finding of this research is that the learning method previously applied at the Raudlatul Ulum 1 Islamic Boarding School is considered ineffective in helping students understand and master the yellowclassical books. The inappropriateness of the method triggered anxiety and disappointment among students, parents, and the pesantren, so that the target of learning to read the yellowIslamic classic book in the pesantren was not achieved. The use of the Al-Miftah method is one of the efforts to overcome this. Although considered effective, the Al-Miftah method still has many shortcomings that need to be addressed to be implemented at the Raudlatul Ulum 1 Islamic Boarding School. The results of this study are expected to provide a good understanding of the implementation of the Al-Miftah method and how to overcome its weaknesses.